Behaviourist-Constructivist Pedagogical Design Possibilities Within the Community of Inquiry Framework - Sareen, Sheriya; Mandal, Sayantan (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
The discourse on blended learning must not take away focus on learning by concentrating explicitly on technologies. When learner-centred discussions are incorporated, these may be confined to constructivist pedagogies, as evident through the well-established community of inquiry (CoI) framework. While a few early advances argue for behaviourist pedagogies to underpin the CoI framework in particular, and a plethora of literature supports behaviourist-constructivist interplay for blended learning in general, this study pioneers the proposal of these interactions within the CoI framework for blended learning. It also challenges the prevailing stand-alone socio-constructivist pedagogical design of the CoI framework to deal with the complexities of higher education by adopting a decolonial positionality. In this light, we explain the impact of missing out on behaviourist designs on the CoI framework through the problem of epistemological untenability and that of assumed learning. Having provided the rationale for including behaviourist designs, we then emphasize the behaviourist-constructivist interactions within the framework. This discussion paper contributes to the ongoing dynamic scholarship of the CoI and encourages the research community to empirically explore the positioning of such a pedagogical design within this framework.